Kontrowersje związane z definicją i charakterem prawnym opłat i podatków ekologicznych - Ptak, Michał (Controversies over the definitions and legal character of environmental charges and taxes, 2007)
The paper presents some definitions of environmental charges and taxes. According to one definitione a tax falls into the environmental category if the “lax base is a physical unit (or a proxy for it) of something that has a proven specific negative impact on the environment”. This definition has been agreed by international experts and adopted by the Statistical Office of the European Communities (Eurostat) and Organisation for Economic Co-operation and Development (OECD). It allows to compare the trends in the taxation of environmental resources in different countries. The article also presents differences between charges (or fees) and taxes both in the legal sense and in respect of their use as environmental policy instruments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 41-52